2018
DOI: 10.1093/mnrasl/sly213
|View full text |Cite
|
Sign up to set email alerts
|

Extreme AGN variability: evidence of magnetically elevated accretion?

Abstract: Rapid, large amplitude variability at optical to X-ray wavelengths is now seen in an increasing number of Seyfert galaxies and luminous quasars. The variations imply a global change in accretion power, but are too rapid to be communicated by inflow through a standard thin accretion disc. Such discs are long known to have difficulty explaining the observed optical/UV emission from active galactic nuclei. Here we show that alternative models developed to explain these observations have larger scale heights and s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
90
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(98 citation statements)
references
References 71 publications
8
90
0
Order By: Relevance
“…More clearly, we propose the appearance of the broad Hα component in the bright AGN regime and disappearance of the broad Hα component in the LLAGN regime. We note that similar scenarios have been proposed in the literature (Noda & Done 2018;Dexter & Begelman 2019a;Ruan et al 2019), although the on-off timescale in CL-AGNs remains a challenging task in this model (Dexter & Begelman 2019a). Based on broadband continuum spectral modeling Noda & Done (2018) suggest that Mrk 1018 underwent a soft-to-hard state transition as it faded from Seyfert 1 to 1.9.…”
Section: Nature Of the Variabilitysupporting
confidence: 64%
“…More clearly, we propose the appearance of the broad Hα component in the bright AGN regime and disappearance of the broad Hα component in the LLAGN regime. We note that similar scenarios have been proposed in the literature (Noda & Done 2018;Dexter & Begelman 2019a;Ruan et al 2019), although the on-off timescale in CL-AGNs remains a challenging task in this model (Dexter & Begelman 2019a). Based on broadband continuum spectral modeling Noda & Done (2018) suggest that Mrk 1018 underwent a soft-to-hard state transition as it faded from Seyfert 1 to 1.9.…”
Section: Nature Of the Variabilitysupporting
confidence: 64%
“…150 R g ) in NGC 7589, a H/R ∼ 0.05 is required so that the predicted viscosity time-scale (4 years for a disc with α = 0.5) matches with the estimated t ADAF→TD (a few years) for NGC 7589. Although such a large H/R is not expected in the thin disc model (H/R should be ∼ 10 −3 ), it can be obtained in the magnetic pressure supported accretion disc model proposed by (Dexter & Begelman 2019). In this model, the disc is geometrically thick at all luminosities which gives a viscous propagation time-scale as short as a few years, consistent with the observed time-scale.…”
Section: Transition From Low State To High Statesupporting
confidence: 76%
“…Begelman & Silk 2017, and references therein) and not only in the upper layers (e.g. Miller & Stone 2000), possibly solving a few long-standing issues of the standard accretions disk theory (Dexter & Begelman 2019). Simulations indeed showed that P mag can become an important competitor in supporting the disk vertically (Bai & Stone 2013;Salvesen et al 2016), although heavily depending on the strength of the net vertical magnetic field, the origin of which is not fully understood, yet.…”
Section: Magnetically-dominated Disksmentioning
confidence: 98%